Rola negocjacji o pracę we współczesnych organizacjach - Kowalczyk, Elżbieta (The role of job negotiations in contemporary organizations, 2006)
In the paper author is focused at the increasing role of the job negotiations in the contemporary organizations. Dynamic changes on the labour market, new and elastic forms of functioning of organizations and permanent improvement of employees are affecting the negotiations process. Author analyzed these problems from the point of view perspective of labour market, firms and job seekers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 631-638